2020
DOI: 10.1097/md.0000000000022467
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent trigeminocardiac reflex in percutaneous balloon compression for trigeminal neuralgia

Abstract: Rationale: Trigeminocardiac reflex (TCR) sometimes occurs during the percutaneous balloon compression (PBC) procedure to treat trigeminal neuralgia (TN), and it manifests as transient bradycardia or sinus arrest. However, recurrent intraoperative TCR cases are rarely reported. Meanwhile, the treatment for recurrent TCR is still unclear. Patient concerns: A 74-year-old male with a 2-year TN history could no longer tolerate the side effects of carbamazepine and came to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Trigeminocardiac reflex can be found during percutaneous procedure to treat trigeminal neuralgia. It presents transient bradycardia or even sinus arrest [10,12]. Our patient did not show any bradycardia during the procedure.…”
Section: Discussionmentioning
confidence: 48%
“…Trigeminocardiac reflex can be found during percutaneous procedure to treat trigeminal neuralgia. It presents transient bradycardia or even sinus arrest [10,12]. Our patient did not show any bradycardia during the procedure.…”
Section: Discussionmentioning
confidence: 48%
“…Third, the hospitalization time is short, and the patient can be discharged from hospital within 2–3 days after operation. Fourthly, the patient is well-tolerated, accepts the whole operation under general anesthesia, and the patient has less pain and discomfort during the operation ( 15 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although PBC-induced TCR has been widely reported, 14 , 15 , 23 the pathophysiology of the TCR has not been well elucidated. Some studies suggested that the stimulation of trigeminal nerve could activate both the sympathetic and the parasympathetic nerve systems, which might result in dramatic changes in hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“… 14 However, the administration of anticholinergic agents sometimes can lead to cardiac arrhythmias or fail to terminate TCR. 15 , 16 Currently, the use of anticholinergic drugs for minimizing TCR-related bradycardia remains disputable. 17 Fortunately, nerve blocks were recommended as a simple and effective strategy to prevent TCR in some relevant studies.…”
Section: Introductionmentioning
confidence: 99%